2015
DOI: 10.1128/jvi.03729-14
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytokinome Analysis for Interferon Response

Abstract: IMPORTANCE Innate immunity to viruses is an early defense system to ward off viruses. One mediator is interferon (IFN), which activates a cascade of biochemical events that aim to control the virus life cycle. In our work, we examined more than 200 cytokines, soluble mediators produced within the body as a result of infection, for the ability to enhance IFN action. We identified enhanced interactions with specific IFNs and cytokines. We also revealed that betacellulin, IL-17, and IL-11 cytokines have the novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Since STAT1 homodimers bind to gamma activation site (GAS) promoter sequences in response to type II IFN (IFN-γ) stimulation, the preservation of STAT1 may prime the cells to respond to type II interferon as the type I response abates. This mechanism is consistent with previous reports of both the induction of a GAS binding factor and GAS promoter driven transcription by IFN-α and IFN-β [91, 92]. Indeed in separate experiments, we observed that induction of a GAS reporter gene by interferon-γ is more pronounced in PDLIM2 K/O cells than in the parental Huh7.5 cells.…”
Section: Discussionsupporting
confidence: 93%
“…Since STAT1 homodimers bind to gamma activation site (GAS) promoter sequences in response to type II IFN (IFN-γ) stimulation, the preservation of STAT1 may prime the cells to respond to type II interferon as the type I response abates. This mechanism is consistent with previous reports of both the induction of a GAS binding factor and GAS promoter driven transcription by IFN-α and IFN-β [91, 92]. Indeed in separate experiments, we observed that induction of a GAS reporter gene by interferon-γ is more pronounced in PDLIM2 K/O cells than in the parental Huh7.5 cells.…”
Section: Discussionsupporting
confidence: 93%
“…IRF-1 plays a critical role in innate antiviral response and the functional response of STAT1α, IFN-γ, and TNF-α to IFN-signaling signifies the cell's proper antiviral potential. 56 , 57 Hence, these ex vivo observations suggest that modest reduction in endogenous IRF-1 level, such as that observed in these HESN women, does not affect host cellular IFN responsiveness, the key antiviral innate function.…”
Section: Resultsmentioning
confidence: 70%
“…BTC transgenic mice also develop urothelial hyperplasia and show sex-dependent reduction in urinary protein content, which appears to be independent of EGFR signaling, suggesting a role for ERBB4 48 . BTC has also been identified as a novel modulator of interferon (IFN) response and enhances the anti-viral action of IFN 49 . In a large cytokine and chemokine screen to modulate IFN responses, BTC was identified as one of the most potent modulators of the IFN response.…”
Section: Aspects Of Individual Ligandsmentioning
confidence: 99%